The Effect of Breastfeeding Duration and Parity on the Risk of Epithelial Ovarian Cancer: A Systematic Review and Meta-analysis - Ho Kyung Sung; Seung Hyun Ma; Ji-Yeob Choi; Yunji Hwang; Choonghyun Ahn; Byoung-Gie Kim; Yong-Man Kim; Jae Weon Kim; Sokbom Kang; Jaehoon Kim; Tae Jin Kim; Keun-Young Yoo; et al. (Korean Society for Preventive Medicine, 2016)
Objectives We conducted a systematic review and meta-analysis to summarize current evidence regarding the association of parity and duration of breastfeeding with the risk of epithelial ovarian cancer (EOC). Methods A systematic search of relevant studies published by December 31, 2015 was performed in PubMed and EMBASE. A random-effect model was used to obtain the summary relative risks (RRs) and 95% confidence intervals (CIs). Results Thirty-two studies had parity categories of 1, 2, and ≥3. The summary RRs for EOC were 0.72 (95% CI, 0.65 to 0.79), 0.57 (95% CI, 0.49 to 0.65), and 0.46 (95% CI, 0.41 to 0.52), respectively. Small to moderate heterogeneity was observed for one birth (p<0.01; Q=59.46; I2=47.9%). Fifteen studies had breastfeeding categories of <6 months, 6-12 months, and >13 months. The summary RRs were 0.79 (95% CI, 0.72 to 0.87), 0.72 (95% CI, 0.64 to 0.81), and 0.67 (95% CI, 0.56 to 0.79), respectively. Only small heterogeneity was observed for <6 months of breastfeeding (p=0.17; Q=18.79, I2=25.5%). Compared to nulliparous women with no history of breastfeeding, the joint effects of two births and <6 months of breastfeeding resulted in a 0.5-fold reduced risk for EOC. Conclusions The first birth and breastfeeding for <6 months were associated with significant reductions in EOC risk.